2019
DOI: 10.1088/1361-6668/ab58b9
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency rotational loss in a high-temperature superconducting bearing and its application in micro-thrust measurement for space propulsion

Abstract: High-temperature superconducting (HTS) magnetic bearings have great potential in the field of rotating machinery, such as flywheels and momentum wheels, because of their low friction and self-stabilizing capability. The study of rotational loss in HTS bearing is of great significance to achieve better efficiency. Previous research indicates that low rotational loss has a close relation with hysteresis loss in HTSs and eddy-current losses in the surrounding metal materials. A low coefficient of friction (<10 −8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Durrell et al reported a trapped field of 17.6 T at the centre of a stack of two GdBa 2 Cu 3 O 7−δ (GdBCO) bulk superconductors at 26 K, with 17.24 T having been achieved previously in an equivalent arrangement of YBa 2 Cu 3 O 7−δ (YBCO) [1,2]. Ring-shaped (annular) bulk superconductors that enable access to these large magnetic fields have been investigated for various applications, such as compact nuclear magnetic resonance [3][4][5][6][7][8][9][10] and for more general applications [11][12][13][14]. However, in situ magnetization on these materials remains a significant challenge and a barrier to practical applications of these technologically important materials.…”
Section: Introductionmentioning
confidence: 99%
“…Durrell et al reported a trapped field of 17.6 T at the centre of a stack of two GdBa 2 Cu 3 O 7−δ (GdBCO) bulk superconductors at 26 K, with 17.24 T having been achieved previously in an equivalent arrangement of YBa 2 Cu 3 O 7−δ (YBCO) [1,2]. Ring-shaped (annular) bulk superconductors that enable access to these large magnetic fields have been investigated for various applications, such as compact nuclear magnetic resonance [3][4][5][6][7][8][9][10] and for more general applications [11][12][13][14]. However, in situ magnetization on these materials remains a significant challenge and a barrier to practical applications of these technologically important materials.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from self-stable suspension and moderate stiffness in the radial and axial directions, bulk high-temperature superconductors (HTS) have many engineering applications, such as maglev trains [1,2], superconducting bearings [3,4], flywheel energy storage (FES) systems [5,6] and high-resolution devices [7,8]. In addition, extensive advances have been made in understanding and reducing rotational losses in HTS magnetic bearings, especially for application in FES systems with a high rotation speed [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their very low rotational drag, applications of HTS bearings have been expanded in some high-precision instruments including accelerometers [15], lunar telescopes [16], sensitive gravimeters [17], polarimeters [18] and micro-force sensing devices [7,10]. The use of HTS magnetic bearings in building a micro-thrust test stand is a relatively new application.…”
Section: Introductionmentioning
confidence: 99%
“…These maglev systems have high load capacity and low motion drag, and the friction coefficient of levitation can almost reach 10 -7 . Low drag and low energy consumption also take it valuable application in high precision instruments [8][9][10]. However, flux pinning provides these HTS systems self-stability, but also limits their degrees of freedom at the same time, thus most of them only can rotate or oscillate in one dimension [11].…”
Section: Introductionmentioning
confidence: 99%